Do We Really Want to Include Disabled People in Society? - Sue Ralph (The Francis de Sales Scientific Society (TNFS.PL), 2022)
In this paper a number of issues are explored to answer the question: "Do we really want to include disabled people in our schools, colleges and societies?" Many questions are raised and such issues are discussed as legislation, media representations of disability, disability hate crime, images of disabled people, employment of disabled people, transport and other facilities, and the Olympics. Reference is made to two DVDs.